EDUKASI 10 PESAN GIZI SEIMBANG SEBAGAI UPAYA PENINGKATAN PENGETAHUAN MASYARAKAT DI PUSKESMAS KOTO PANJANG IKUA KOTO KOTA PADANG - Muhammad Rizki Saputra; Bun Yurizali; Rahma Triyana; Ruhsyahadati Ruhsyahadati; Nana Liana; Rifkind Malik; Roland Helmizar; Suharni Suharni; Sri Wahyuni; Alif Dhuha (Yayasan Nusantara Hasana Berdikari, 2026)
Nutritional problems remain one of the major public health challenges in Indonesia. Limited public knowledge regarding healthy eating patterns can increase the risk of various health problems among both children and adults. This community service activity aimed to improve community knowledge regarding the 10 Messages of Balanced Nutrition through health education. The activity was conducted at Koto Panjang Ikua Koto Primary Health Center, Padang City, involving 45 participants consisting of fathers, mothers, and children. The methods used included educational presentations and interactive question-and-answer sessions. The results showed that participants were highly enthusiastic throughout the activity. The high level of participation during discussions indicated increased interest and awareness of the importance of implementing balanced nutrition principles. This educational intervention successfully enhanced participants’ understanding of diverse food consumption, physical activity, clean and healthy living behaviors, and regular nutritional status monitoring. This community service activity is expected to contribute to improving healthy lifestyle behaviors and the overall health quality of the community.